2006
DOI: 10.1097/01.ccm.0000242520.50665.9f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neurally adjusted ventilatory assist and positive end-expiratory pressure on breathing pattern in rabbits with acute lung injury*

Abstract: Acute lung injury can cause a vagally mediated atypical diaphragm activation pattern in spontaneously breathing rabbits. Modulation of PEEP facilitates development of phasic diaphragm electrical activity, whereupon implementation of NAVA can efficiently maintain unloading of the respiratory muscles without delivering excessive tidal volume in rabbits with intact vagal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 53 publications
9
93
2
2
Order By: Relevance
“…11 In contrast to PSV, NAVA prevents excessive P aw and V T values, because EAdi undergoes down-regulation in response to increasing assistance levels, thereby decreasing the amount of assistance provided. 13,14,19,48,49 In a recent comparison of the impact of NAVA and PSV on sleep architecture, we demonstrated that NAVA provided better sleep quality in terms of REM sleep, fragmentation index, and ineffective efforts in unsedated adults. 18 NAVA also allows considerable variability in the breathing pattern (ie, better replicates the variability of spontaneous breathing).…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast to PSV, NAVA prevents excessive P aw and V T values, because EAdi undergoes down-regulation in response to increasing assistance levels, thereby decreasing the amount of assistance provided. 13,14,19,48,49 In a recent comparison of the impact of NAVA and PSV on sleep architecture, we demonstrated that NAVA provided better sleep quality in terms of REM sleep, fragmentation index, and ineffective efforts in unsedated adults. 18 NAVA also allows considerable variability in the breathing pattern (ie, better replicates the variability of spontaneous breathing).…”
Section: Discussionmentioning
confidence: 99%
“…In 3-kg rabbits, Allo et al 56 found that NAVA could effectively unload respiratory muscles without increasing tidal volume. NAVA, compared to PSV, also decreased diaphragm electrical activity and transdiaphragmatic pressure-time product (P Ͻ .05) in lung-injured rabbits, 57 and reduced the incidence and severity of ventilator-induced lung injury in rabbits.…”
Section: Animal Datamentioning
confidence: 99%
“…Titration of the PEEP level in accordance with the EA di signal could optimize the respiratory pattern and reduce tonic diaphragm activity, allowing the patient to maintain spontaneous ventilation in NAVA. 30,31 Observational data from small populations suggest that NAVA in these patients is feasible and seems well tolerated. 32,33 …”
Section: Titration Of the Peep Level And Tonic Diaphragm Activitymentioning
confidence: 99%